Structural Rubberwood LVL : An Engineered Wood Product for Prefabricated Timber Roof Truss - Chee, Yuh Sheng (2003)
Timber roof truss system is one of the major structural application of timber in the housing industry in the country. Since its introduction into the local roof market in 1975, prefabricated timber roof truss system have earned a good reputation as they are designed using advanced structural engineering principles. The timber species such as Balau, Kekatong, Keranji, Resak, Merbatu and Kempas, are commonly preferred or specified to be used for roof truss fabrication. These species are belonged to the strength groups of SG 1 to 8G4, in accordance to timber strength grouping in MS 544 : Part 2 : 2001. However in recent years, the supply of these excellent strength wood species has been declining due to gradual depletion of natural forest and the reduction of logs production. On the other hand, the demand for timber in the prefabricated timber roof truss industry is continue to grow. As a result, lesser-known timber species and lower strength groups timber, commonly grouped under 'chap char' in the local timber trade, were 'conveniently' mixed and supplied into the market. If this situation continue to be unchecked and not properly addressed, it will bring serious adverse implication to the local timber trade and industry. Therefore a long term solution, an alternative structural material for the timber roof truss industry, should draw attention and concern to conduct research in this area. The purpose of this paper is to determine the structural properties of LVL made from Rubberwood and Radiata Pine. These structural LVL were manufactured by CHG Plywood Sdn. Bhd. 's LVL plant and the specimens were send to UiTM Shah Alam for strength properties test. The test were conducted in accordance to A8INZ8 4063 : 1992. The results show that Rubberwood L VL falls in the 8G4 category which is compatible to Resak, Kapur, Kasai and some of Meranti species, and its bending strength properties is superior than LVL made from Radiata Pine. The paper conclude that Rubberwood LVL poses sound structural properties which can provide an alternative material for the prefabricated timber roof truss industry in the country.